History and Application of Piercing the Corporate Veil Doctrine: A Comparison Study between the United Kingdom and Indonesia - Kamaluddin, Muhammad Aqil (Jurist-Diction, 2025)
Separate legal entity doctrine is a foundation in corporation law, and courts have generally resisted deviations from it, save in specific instances involving doctrine of piercing of the corporate veil (PCV). PCV doctrine permits a party to circumvent the separate legal personality and hold the company's "controller" liable. This essay will explain the evolution and future of PCV in UK and Indonesian law. Research methods that will be used are normative and comparative law methods. UK cases have developed PCV doctrine, such as the Rossendale case, which the court argues that not every case requires the doctrine. While Indonesia’s law system implicitly regulated the doctrine under Art. 3 (2) Law Number 40 of 2007 and no major cases. For the future of the doctrine, the UK judges maintained a firm commitment to limited liability and separate legal personality, which means the doctrine’s future looks uncertain. While in Indonesia, there is a lack of highlighting and balancing the separate legal entity with piercing the corporate veil.